Sliding Mode Congestion Control for Data Center Ethernet Networks - Jiang, Wanchun; Ren, Fengyuan; Shu, Ran; Wu, Yongwei; Lin, Chuang (IEEE transactions on computers, 2015)
Recently, Ethernet is enhanced as the unified switch fabric of data centers, called data center Ethernet. One of the indispensable enhancements is end-to-end congestion management, and currently quantized congestion notification (QCN) has been ratified as the corresponding standard. However, our experiments show that QCN suffers from large oscillations of the queue length at the bottleneck link such that the buffer is emptied frequently and accordingly the link utilization degrades, with certain system parameters and network configurations. This phenomenon is corresponding to our theoretical analysis result that QCN fails to enter into the sliding mode motion (SMM) pattern with certain system parameters and network configurations. Knowing the drawbacks of QCN and realizing the advantage that congestion management system is insensitive to the changes of parameters and network configurations in the SMM pattern, we present sliding mode congestion control (SMCC), which can enter into the SMM pattern under any conditions. SMCC is simple, stable, fair, has short response time, and can be easily used to replace QCN because both of them follow the framework developed by the IEEE 802.1Qau work group. Experiments on the NetFPGA platform show that SMCC is superior to QCN, especially when traffic pattern and network states are variable.